The Social Gap Index and the prevalence of osteoarthritis in the community: a cross-sectional multilevel study in Mexico (2016)
Multilevel studies have gained importance for highlighting social inequalities in health. These associations have been reported previously in diseases such as arthritis and chronic pain. We conducted a cross-sectional study using multilevel analysis to identify individual and contextual factors associated with the variation of prevalence of osteoarthritis (OA) in the Mexican population. The sample included 17,566 individuals of which 10,666 (60.7 %) were women. The relationship between individual and contextual factors and OA were analyzed with a multilevel strategy.